Seroma formation after modified radical mastectomy - Mahmoud AboAmra (Wolters Kluwer Medknow Publications, 2017)
Background Modified radical mastectomy remains the most commonly performed surgery for breast cancer. Aim of the work The aim of this study was to evaluate the effect of different methods (conventional scalpel, electrocautery, and harmonic scalpel) of breast dissection during mastectomy on seroma formation. Patient and methods This study was conducted in Al-Azhar University Hospital in Assiut from April 2013 to April 2016, on 110 female patients aged from 25 to 70 years; all patients were having stage II breast cancer, according to the Manchester and International Union against Cancer (TNM). Modified radical mastectomy was done after complete preoperative assessment. Result One-hundred and ten female patients have stage II breast cancer aged from 25 to 70 years. During the modified radical mastectomy, in this study, the breast dissection was done by electrocautery in 42 patients, using conventional scalpel in another 42 patients and using harmonic scalpel in the remaining 26 patients. At the end of this study, there were 15 cases (out of 110 patients) of postmastectomy seroma detected postoperatively, only one case in the conventional scalpel group, 14 cases in the electrocautery group and no case in the harmonic scalpel group. The wound drains were removed in all cases on day 7postoperatively. In all patients of this study, a pressure garment was used postoperatively. Conclusion The use of harmonic scalpel in breast dissection is better than electrocautery use as regards postmastectomy seroma formation. If harmonic scalpel is not available, it is better to use the conventional scalpel.